Behavior of N‐oxide derivatives in atmospheric pressure ionization mass spectrometry. (12th February 2013) - Ibrahim, Hany; Couderc, François; Perio, Pierre; Collin, Fabrice; Nepveu, Françoise
<x xml:space="preserve">Abstract</x> RATIONALE Indolone‐N‐oxide derivatives possess interesting biological properties. The analysis of these compounds using mass spectrometry (MS) may lead to interference or under‐estimation due to the tendency of the N‐oxides to lose oxygen. All the previous works focused only on the temperature of the heated parts (vaporizer and ion‐transfer tube) of the mass spectrometer without investigating other parameters. This work is extended to the investigation of other parameters. METHODS The behavior of N‐oxides during atmospheric pressure chemical ionization (APCI) and electrospray ionization (ESI) has been investigated using MSn ion trap mass spectrometry. Different parameters were investigated to clarify the factors implicated in the deoxygenation process. The investigated parameters were vaporizer temperature (APCI), ion‐transfer tube temperature, solvent type, and the flow rates of the sheath gas, auxiliary gas, sweep gas and mobile phase. RESULTS The deoxygenation increased when the vaporizer temperature increased. The extent of the 'thermally' induced deoxygenation was inversely proportional to the ion‐transfer tube temperature and auxiliary gas flow rate and in direct proportion to the mobile phase flow rate. Deoxygenation was not detected under MS/MS fragmentation and hence it is a non‐collision‐induced dissociation. N‐Oxides have the tendency to form abundant 'non‐classical' dimers under ESI, which fragment via dehydration rather than giving their corresponding monomer. CONCLUSIONS Deoxygenation is not solely a 'classical' thermal process but it is a thermal process that is solvent‐mediated in the source. Deoxygenation was maximal with an APCI source while dimerization was predominant with an ESI source. Therefore, attention should be paid to these molecular changes in the mass spectrometer as well as to the choice of the ionization mode for N‐oxides. Copyright © 2013 John Wiley & Sons, Ltd.